The safety of low-molecular-weight heparins in the prevention of venous thromboembolism in surgically-treated cancer patients: results of a multicentre observational study - Olesiński, Tomasz; Fijałkowska, Anna; Rutkowski, Andrzej (Contemporary Oncology/Współczesna Onkologia, 2017)
Aim of the study : Despite widespread use of pharmacological prophylaxis, venous thromboembolism (VTE) still constitutes a common complication in cancer patients. The aim of the study was to analyse the safety of low-molecular-weight heparins (LMWH) in the prevention of VTE in surgically-treated cancer patients. Material and methods : A total of 5207 cancer patients (44.5% men and 55.5% women) aged 16–97 years participated in a prospective observational study conducted in 13 Polish cancer centres in 2005–2008. This cohort included 4782 subjects who were treated surgically and received LMWH as a pharmacological prophylaxis for VTE prior to or after the surgery. The incidence of haemorrhagic complications and thrombocytopaenia was analysed in this cohort, along with intra-hospital mortality. Results: Mean duration of LMWH administration was 9.4 ±7.8 days. Haemorrhagic complications: heavy (n = 15) or light bleeding (n = 299), were observed in 314 patients (6.5%). A total of 314 patients (6.5%) presented with haemorrhagic complications: heavy (n = 15, 0.3%) or light bleeding (n = 299, 6.3%). Four cases of heavy bleeding: gastrointestinal bleeding (n = 2), retroperitoneal bleeding (n = 1), and central nervous system bleeding (n = 1), were classified as definitely related to LMWH. No significant association was found between the incidence of haemorrhagic complications and the type of administered LWMH (p = 0.523). No cases of thrombocytopaenia or deaths related to administration of LMWH were reported. Conclusions : LMWH seems to be a safe form of pharmacological prophylaxis for VTE in surgically-treated cancer patients.